Diagnosis for Community Education of Oregano and Damiana in the Community of Camargo. - Hernández, Jorge Arturo Velázquez; Chombo, Rosalía Alonso; Guevara, Epigmenio Muñoz (Advances in Social Sciences Research Journal, 2023)
The objective of the present investigation is to show the results obtained in the community training that was carried out with residents of the Camargo community in Peña Miller, where the objective was to provide the tenants with the necessary tools and knowledge to take advantage of the oregano resources and the damiana as inputs for the elaboration of products that help them improve their economic situation. The methodology used is of a quantitative nature, related to the type of sample for convenience due to the very small universe that was had due to the restrictions of the health contingency that was experienced worldwide. The characteristics of the population are varied, all women of various ages and occupations. Finally, it is concluded that the practices that are carried out in the community, as well as their customs and traditions are of vital importance for the inhabitants because they are an inexhaustible source of knowledge and economic collection for their subsistence. It is clear that natural resources still prevail that can be exploited and processed to become sources of help and improvement for people, therefore it is necessary to offer training that provides them with the necessary strategies that help them have a different vision where they can glimpse the various alternatives that they have as a source of work.